Enhancing Oral and Written Language for Adolescents and Young Adults with Down Syndrome - Pelatti, Christina Yeager (Seminars in Speech and Language, 2015)
Oral and written language development for adolescents and young adults with Down syndrome (Ds) are particularly challenging. Yet, research supports a syndrome-specific profile highlighting strengths and particular areas of difficulty for this group of individuals. For example, adolescents and young adults with Ds tend to understand more than they produce. In terms of oral language development, the domains of semantics and pragmatics are relative strengths whereas morphosyntax is particularly difficult. Much less is known about written language development because most adolescents and young adults with Ds are at the emergent literacy or word identification (i.e., ability to recognize and name single words) stages; however, relative strengths emerge in the area of word identification. The purpose of this article is to explore the research findings on oral and written language strengths and weaknesses and intervention strategies and techniques that facilitate development in these two interrelated domains. In addition, a case study example is provided to further enhance the clinical skills of speech-language pathologists who work with this population.
Keywords: Down syndrome; adolescents; young adults; oral language; written language